Integrating land use simulation and carbon assessment for sustainable urban planning in Fuzhou metropolitan area using PLUS and InVEST models - Qiuyi Zhang; Ronghui Huang; Changhua Zhu; Liyun Huang; Di Yang (Scientific Reports)
Abstract In the pursuit of sustainable urban planning, integrating land use simulation with carbon storage assessment is crucial for achieving the “dual carbon” goals. This study focuses on the Fuzhou Metropolitan Area, utilizing land use data from 2000, 2010, and 2020. By establishing three future development scenarios—natural, urban, and dual-carbon target scenarios—based on the “Fuzhou Metropolitan Area Development Plan,” this research employ the Patch-generating Land Use Simulation (PLUS) and the Integrated Valuation of Ecosystem Services and Trade-offs (InVEST) models. The analysis reveals that from 2000 to 2020, the areas of cultivated land, forest land, grassland, and water bodies decreased, while construction land and bare land increased. Notably, the nighttime lighting factor significantly impacts land use changes, with elevation playing a crucial role in changes to water bodies and bare land. Under natural and urban development scenarios, carbon storage exhibits a downward trend, whereas the dual-carbon target scenario limits construction land expansion and reverses this trend, resulting in increased carbon storage. Based on these insights, this study proposes a three-stage urban planning strategy: strengthening carbon assessment in the early stages, fostering cross-departmental collaboration during implementation, and ensuring dynamic monitoring and adaptive adjustments in the later stages. This approach aims to harmonize urban development with ecological conservation, thereby maximizing economic and ecological benefits and supporting the achievement of the “dual carbon” policy goals.